A Spanish Sign Language (LSE) Adaptation of the Communicative Development Inventories. (18th October 2019) - Rodríguez-Ortiz, Isabel R; Pérez, Mar; Valmaseda, Marian; Cantillo, Coral; Díez, M Aránzazu; Montero, Ignacio; Moreno-Pérez, F Javier; Pardo-Guijarro, María Jesús; Saldaña, David
Abstract: This article presents the adaptation of the MacArthur Communicative Development Inventory (CDI; Fenson et al., 1993, Guide and technical manual for the MacArthur Communicative Development Inventories. San Diego, CA: Singular Press; Fenson et al. 1994, Variability in early communicative development. Monographs of the Society for Research in Child Development, 59, 1–173) to Spanish Sign Language (LSE). Data were collected from 55 participants (32 boys and 23 girls; 17 deaf signers, 38 hearing signers) who, evaluated by their caregivers every 4 months, presented a total of 170 records. The parents reported the signs that the children could understand or produce between 8 and 36 months. Results suggested that the CDI adapted to LSE is a valid and reliable instrument. Signing children could understand more signs than they produced at this early developmental stage. There were no significant differences between boys and girls, or between deaf and hearing children. The development of LSE is similar to other sign languages, although with a lower production of signs in the early stages, perhaps due to the bilingualism of most of the children of our study.